Evaluasi dan Perbaikan Tampilan Website Taman Rekreasi Sengkaling UMM Dengan Metode Human Centered Design (HCD) - Ahmad Isa Hambali; Admaja Dwi Herlambang; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Website Wisata Sengkaling is owned by Taman Rekreasi Sengkaling UMM. Website that has some problems in writing on the website, content layout and inappropriate color selection. The focus of this research is how to improve the appreance of the interface design on Wisata Sengkaling. Usability evaluation in this study uses the Website Usability Evaluation (WEBUSE) with four categories, that is Content, Organisation and Readability, Navigation and Links, User Interface Design and Performance and Effectiveness. The repair method used is the Human Centered Design (HCD). The discussion in the study is specify the context of use, specify the user requirement, produce design solution and evaluate the design solution. The result of this study indicate that the design of solution made using the Human Centered Design method is better than the initial design. Evaluation in old design in the Content, Organisation and Readability category have value 0,57. In the Navigation and Links category have value 0,57. In the User Interface Design category have value 0,54. In the Performance and Effectiveness category have value 0,55. But, on new design solution in the Content, Organisation and Readability category have value 0,65. In the Navigation and Links category have value 0,64 In the User Interface Design category have value 0,66. In the Performance and Effectiveness category have value 0,66.